GUIDELINES FOR DISASTER PREVENTION AND MITIGATION IN A SOCIO-CULTURAL CONTEXT IN MAHA SARAKHAM PROVINCE - Chinphakdi, Rangsan; Suk-Erb, Somkhit (Journal of Buddhist Anthropology, 2022)
The Objectives of this research article were to disaster prevention and mitigation approaches in social and cultural contexts in Maha Sarakham Province. The researcher used a qualitative research method. By studying the documents and studying in the field By observation and in-depth interviews with a sample of 192 people, consisting of a provincial municipality disaster prevention and mitigation supervisor, 1 district defense supervisor, 2 disaster prevention and mitigation officers, a foundation entrepreneur who has been certified Quality, 5 people, bailiffs for disaster prevention and mitigation, 13 people, 170 people who came to request services and presented by descriptive analysis. The results showed that disaster prevention and mitigation approaches in the social-cultural context of Maha Sarakham Province are very important to Must receive cooperation as follows: 1) Build a network of cooperation between the public and private sectors. That is, they are reciprocal and must not affect the independence or individuality of people or organizations. develop to a level of joint action to achieve common goals. 2) There must be sustainability of the network. Activities are carried out continuously until such activities become a clear pattern of actions that are generally accepted by the members of the network. 3) Maintaining good relations between network members. Must build good relationships to maintain the network to be sustainable and 4) Establishing mechanisms to create incentive systems. Certain mechanisms need to be established to help motivate members to participate. There is a good cooperation that will be a way to create sustainability for the organization in working to help society.